2021
DOI: 10.4240/wjgs.v13.i11.1497
|View full text |Cite
|
Sign up to set email alerts
|

Is omentectomy necessary in the treatment of benign or malignant abdominal pathologies? A systematic review

Abstract: BACKGROUND The omentum is an organ that is easily sacrificed during abdominal surgery. The scope of omentectomy and whether a routine omentectomy should be performed are still unknown. AIM To review the literature in order to determine the physiological functions of the omentum and the roles it plays in pathological events in order to reveal the necessity for removal and preservation of the omentum. METHODS A clinical review of the English la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(55 reference statements)
0
3
0
1
Order By: Relevance
“…The omentum is an organ with widely described properties, including control of intra-abdominal infectious and inflammatory processes, angiogenesis, and wound healing promotion, as well as a key role in tumor spread, thus being characterized as "the abdominal policeman" [31]. It also holds a crucial role as a reconstructive tool, since omental flaps are commonly used for reinforcement of esophagogastric anastomosis after open or minimally invasive esophagectomy, taking advantage of its anatomical and physiological characteristics [10].…”
Section: Omentoplasty Of the Anastomosismentioning
confidence: 99%
“…The omentum is an organ with widely described properties, including control of intra-abdominal infectious and inflammatory processes, angiogenesis, and wound healing promotion, as well as a key role in tumor spread, thus being characterized as "the abdominal policeman" [31]. It also holds a crucial role as a reconstructive tool, since omental flaps are commonly used for reinforcement of esophagogastric anastomosis after open or minimally invasive esophagectomy, taking advantage of its anatomical and physiological characteristics [10].…”
Section: Omentoplasty Of the Anastomosismentioning
confidence: 99%
“…Este proceso se caracteriza por la formación de una masa inflamatoria alrededor del apéndice inflamado, compuesta por tejido inflamado, vísceras adyacentes y epiplón mayor. El plastrón actúa como una barrera física que limita la propagación de la infección hacia la cavidad abdominal, evitando así la peritonitis generalizada (12).…”
Section: Fisiopatología Del Plastrón Apendicularunclassified
“…Furthermore, there is a lack of consensus as to the amount of healthy omental tissue that should be removed in patients who present without overt metastasis. One school of thought has advocated omental biopsies rather than removal of the omentum in these cases, as omentectomy may have complications such as increasing the risk of sepsis, adhesive bowel obstruction, and splenic injury (10)(11)(12)(13)(14). In support of this line of thinking, a study using a rat model of ovarian cancer found that prophylactic omentectomy did not improve survival (15).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that normal saline stimulates the receptivity of the omentum for cancer cells and that the risk of colonization can be minimized by using a biocompatible crystalloid for lavage procedures. JCI Insight 2023;8 (12):e167336 https://doi.org/10.1172/jci.insight.167336…”
Section: Introductionmentioning
confidence: 99%